2014
DOI: 10.1530/erc-13-0480
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of ERβ and prostate tumorigenesis in FGF8b transgenic mice

Abstract: Estrogens contribute to the development and growth of the prostate and are implicated in prostate tumorigenesis. In their target tissues, estrogens mediate their effects via estrogen receptor a (ERa (ESR1)) and b (ERb (ESR2)). Hyperplasia and decreased differentiation of epithelial cells in the prostate have been reported in ERb knockout (BERKO) mice. Herein, we studied the effect of ERb deficiency on prostate tumorigenesis by crossing BERKO FVB mice with prostate-targeted human fibroblast growth factor 8b tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Specifically, it was reported recently that deletion of ERβ in the FGF8b transgenic model of prostate tumorigenesis did not increase tumor incidence (Elo et al, 2014). Although the authors discounted a tumor suppressive role for ERβ based on these data, this conclusion should be tempered by the likely possibility that FGF8b-mediated tumorigenesis involves repression of ERβ, similar to our finding with prostate tumorigenesis caused by PTEN deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it was reported recently that deletion of ERβ in the FGF8b transgenic model of prostate tumorigenesis did not increase tumor incidence (Elo et al, 2014). Although the authors discounted a tumor suppressive role for ERβ based on these data, this conclusion should be tempered by the likely possibility that FGF8b-mediated tumorigenesis involves repression of ERβ, similar to our finding with prostate tumorigenesis caused by PTEN deletion.…”
Section: Discussionmentioning
confidence: 99%
“…These mice do not develop prostate cancer (Antal et al, 2008; Imamov et al, 2004), although some studies have observed prostate hyperplasia in older BERKO mice (Imamov et al, 2004). Furthermore, deletion of ERβ in the FGF8b transgenic model of prostate tumorigenesis did not increase tumor incidence, a finding that has been used to discount a tumor suppressive function for ERβ (Elo et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The role of ERβ in oppressing androgen receptor signaling, and suppressing proliferation and inflammation, suggests that ERβ may be a potential therapeutic target to prevent the progression of prostate cancer (30). Differentiation of prostatic epithelial cells, in which ERβ serves a significant role, is a defensive mechanism required for the protection against inflammation in the prostate of FGF8b transgenic mice (31). The findings of the present study revealed that ERβ overexpression reduced the upregulated expression levels of TNF-α, MCP-1, IL-6 and IL-1β in PC-3 cells induced by LPS, indicating a potential therapeutic role of ERβ in the reduction of inflammation in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One study described CAF ERa and ERb expression as a marker of clinically advanced disease. 50 On the other hand, some studies have shown that estrogen-sensitive CAFs can suppress tumor growth, invasion, and metastasis through reduced IL-6 and C-C motif chemokine ligand 5 expression. 51,52 Innate Immune Cells…”
Section: Stromamentioning
confidence: 99%